WORK MOTIVATION OF STAFF FRONT OFFICE SERVICES IN TJOKRO HOTEL PEKANBARU - Rina Chesia Megaria; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is about motivation of employees in performing front office services at Tjokro Hotel Pekanbaru. This research aims to (1) find out the factors that affect employee work motivation in performing front office services at Tjokro Hotel Pekanbaru. (2) To find out efforts that can be made by the company in increasing the motivation and productivity of employees' work in performing front office services at Tjokro Hotel Pekanbaru The sample in this study amounted to 6 people using census sampling techniques. This study uses quantitative descriptive methods to group data and then neatly arranged using frequencies. And for data collection techniques in this study using interviews and questionnaires. By using the likert scale as a measuring instrument. Based on the results of research obtained on motivation of employees work in performing front office services at tjokro hotel pekanbaru is in the good category. This is obtained by obtaining a total score of 413 points. Keywords : Motivation, Hotel, Front Office